Pengaruh Metode Ekstraksi Sari Nanas Secara Langsung Dan Osmosis Dengan Variasi Perebusan Terhadap Kualitas Sirup Nanas ( Ananas comosus L. ) - Tri Sulismuji Wiyono; Diah Kartikawati (Serat Acitya, 2017)
Pineapple fruit is a fruit that quite easily damaged. Alternative actions that can be done to address the problem is to process the fruit into various refined products. Pineapples can be processed into syrup by using two types of extraction which are extraction directly and osmosis. Excess extraction by osmosis method is not using expensive equipment, the manufacturing process is easy and does not use chemicals that are safe for consumption.This research is compiled using a completely randomized design (CRD) factorial pattern consisting of two factors with 2 levels of treatment and repeated 3 times. The first factor is the method of extraction (E) consists of two levels: Direct (M1) and Osmosis (M2). The second factor is the boiling method (P) consists of two levels: without lid (P1) and the lid (P2). Osmosis extraction method by means of a closed boiling produces the value of total dissolved solids, sugar and pineapple syrup vitamin C content highs, respectively 3.86 g / 100g; 44.60% and 3.74 mg / 100ml. Viscosity, total acid and pH values are not affected by the extraction method and means boiling the pineapple syrup. Direct extraction method by means of a closed boiling produces the highest water content (64.83%) and the lowest sugar content (32.20 g / 100g).